Uji Toksisitas Ekstrak Kelopak Jantung Pisang Kepok (Musa Paradisiaca Linn.) dengan Metode BSLT (Brine Shrimp Lethality Test) - Kalmud Nia Tekha; Erwin -; Rudi Kartika (JURNAL KIMIA MULAWARMAN, 2015)
The phytochemical tests and toxicity test extract from petals of kepok banana flowers (Musa paradisiaca Linn.) have been researched. The method used is Brine Shrimp Lethality Test (BSLT). According the results of phytochemicals test from petals of the kepok banana flowers (Musa paradisiaca Linn.) contains compounds metabolite secondary which is alkaloids, saponin and triterpenoid. The toxicity test showed the most active fraction is the ethanol fraction with 304.8067 ppm of LC50 values.Keywords: Musa paradisiaca Linn., phytochemical test, toxicity test (BSLT)